2005
DOI: 10.1007/s10535-005-5091-2
|View full text |Cite
|
Sign up to set email alerts
|

Differences in antioxidant activity in response to salinity stress in tolerant and susceptible wheat genotypes

Abstract: Effects of long-term sodium chloride salinity (100 and 200 mM NaCl; ECe = 6.85 and 12.3 dS m -1 ) were studied in tolerant (Kharchia 65, KRL 19) and susceptible (HD 2009, HD 2687) wheat genotypes. NaCl decreased relative water content (RWC), chlorophyll content (Chl), membrane stability index (MSI) and ascorbic acid (AA) content, and increased the contents of hydrogen peroxide, thiobarbituric acid reactive substances (TBARS), and activities of superoxide dismutase (SOD), ascorbate peroxidase (APOX) and glutath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
213
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 396 publications
(250 citation statements)
references
References 34 publications
33
213
1
3
Order By: Relevance
“…It is clear that high level of endogenous AsA is essential effectively to maintain the antioxidant system that protects plants from oxidative damage due to abiotic and biotic stresses (Shigeoka et al, 2002). Salt induces a decrease in AsA content in wheat at the vegetative stage (Sairam et al, 2005) and at the reproductive stage (Athar et al, 2008). In agreement with this observation, our study showed that salinity induces a decrease in AsA in the two durum wheat cultivars particularly in the cv.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…It is clear that high level of endogenous AsA is essential effectively to maintain the antioxidant system that protects plants from oxidative damage due to abiotic and biotic stresses (Shigeoka et al, 2002). Salt induces a decrease in AsA content in wheat at the vegetative stage (Sairam et al, 2005) and at the reproductive stage (Athar et al, 2008). In agreement with this observation, our study showed that salinity induces a decrease in AsA in the two durum wheat cultivars particularly in the cv.…”
Section: Discussionsupporting
confidence: 87%
“…Parallel to our results, low MDA content is important in terms of salt tolerance as represented in different studies. Salt tolerant barley (Liang et al, 2003), tobacco (Ruiz et al, 2005) and wheat cultivars (Sairam et al, 2002(Sairam et al, , 2005Mandhania et al, 2006) also showed low level of lipid peroxidation which is important sign of higher oxidative damage limiting capacity under salinity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The excessive accumulation of ROS under drought stress might have caused injury to cells in drought sensitive conventional plants. Injuries caused by ROS include lipid peroxidation, degradation of membrane protein and inactivation of enzymes such as those responsible for photorespiration (example RUBiSco, PEP carboxylase) which are important components in the electron transport chain (Sairam et al, 2005;Zlatev and Lidon, 2012).…”
Section: Discussionmentioning
confidence: 99%